Importance of the structure of paper support in gas transfer properties of protein‐coated paper. Issue 4 (8th June 2013) - Cagnon, Thibaut; Guillaume, Carole; Gastaldi, Emmanuelle; Gontard, Nathalie
ABSTRACT Composite materials made from fibrous support coated with agro‐polymers are widely commercialized for different applications. But, their transfer properties have only been sparingly studied despite their importance in membrane technologies or food packaging. Furthermore, most of past studies on the topic have been focused on the impact of surface properties of the support on the final coated material structure and its properties; leaving unexplored the potential impact of the in‐bulk structure of the support. This study demonstrated the influence of in‐bulk structure and especially fibers refining degree of 4 kraft papers (SP28, 36, 60, and 80) on the structure, and surface and gas transfer properties of their respective wheat gluten (WG) coated papers (WGP28, 36, 60, and 80). Paper presenting a high fibers refining degree (SP28) exhibited very tight and narrow in bulk fibers network which prevented most of the WG‐coated layer penetration, maintaining an important WG apparent layer on top of the paper and a small fibers/wheat gluten composite zone inside (WGP28). Such structure gave strong "WG‐like" properties to the final coated material with moderate oxygen permeation and high permselectivity (1.50 × 10−11 mol m−2 s−1 Pa−1 and 8.09, respectively for WGP28) whereas the highly impregnated structure of coated papers built on lowly refined papers (SP80, with wide and loose structure) gave coated materials presenting weak "WG‐like" properties, supposedly due to a thick composite zone presenting interfacial defects, with higher oxygen permeation and very limited permselectivity (11.90 × 10−11 mol m−2 s−1 Pa−1 and 1.06, respectively for WGP80). © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2848–2858, 2013